Dissimilar friction stir lap welding of AA2198-AA6082: Process analysis and joint characterization. (November 2021) - Tucci, Fausto; Carlone, Pierpaolo; Silvestri, Alessia Teresa; Parmar, Hetal; Astarita, Antonello
Abstract: This paper deals with the dissimilar friction stir lap welding of AA2198 and AA6082 thin sheets. The influence of processing parameters, namely welding speed and tool rotational speed on joint features, microstructure, and mechanical properties were investigated by implementing a full factorial design of experiments. During the welding process, axial and transversal forces were continuously measured using a dedicated fixture equipped with sensors aiming at the correlation of this processing parameter with the quality of the achieved joints. The microstructural analysis provided a detailed view of the metallurgical features such as hook, and its relative influence exhibited on the welded joints. Microhardness distribution and lap shear behavior were assessed and correlated with the metallurgical analysis.